(untitled) (Південний архів (історичні науки), 2025)
This paper explores the historical development of the Carolingian-type European sword, which gained prominence during the Early Middle Ages (8th–11th centuries). Particular attention is given to the analysis of the structural features of Carolingian swords, as well as their symbolic and functional roles within military and cultural contexts.The purpose of the study is to examine the transformation of the sword as a pivotal military and socio-cultural phenomenon of the Early Middle Ages, with a focus on intercivilizational contacts between the West and the East. The article includes an analysis of the archaeological find known as the “Sword of Sviatoslav”, which has become a subject of ongoing scholarly debate. The study also addresses the sword’s role as a marker of social prestige and authority, particularly in the context of funerary practices, which underscore its symbolic significance in the warrior culture of the period. To achieve its objectives, the research employs contemporary methodological frameworks, integrating both general and specialized academic approaches. The synthetic nature of the methodology has made it possible to draw conclusions relevant to the broader discourse on the evolution of long-bladed weaponry in the Early Middle Ages, especially the Carolingian sword. Research results. This paper traces the evolution of the European sword from the Roman spatha to the Carolingian type, interpreting it as a key element in the military and social history of the era.Through the examination of structural, functional, and symbolic characteristics, the study reveals the sword’s importance in warfare, cultural traditions, and ritual practices. Conclusions. Archaeological materials and written sources allow the sword to be interpreted as a symbol of authority, social status, and spiritual identity, while its presence in burial contexts signifies prestige and sacral meaning. The research emphasizes the sword’s cultural relevance among warrior elites in the territory of present-day Ukraine during the Early Middle Ages and outlines prospects for further scholarly inquiry into this subject.